A Mechanosensitive Channel Governs Lipid Flippase-Mediated Echinocandin Resistance in Cryptococcus neoformans - Chengjun Cao; Yina Wang; Seema Husain; Patricia Soteropoulos; Chaoyang Xue (mBio, 2019)
ABSTRACT Echinocandins show fungicidal activity against common invasive mycoses but are ineffective against cryptococcosis. The underlying mechanism for echinocandin resistance in Cryptococcus neoformans remains poorly understood but has been shown to involve Cdc50, the regulatory subunit of lipid flippase. In a forward genetic screen for cdc50Δ suppressor mutations that are caspofungin resistant, we identified Crm1 (caspofungin resistant mutation 1), a homolog of mechanosensitive channel proteins, and showed that crm1Δ restored caspofungin resistance in cdc50Δ cells. Caspofungin-treated cdc50Δ cells exhibited abnormally high intracellular calcium levels ([Ca2+]c) and heightened activation of the calcineurin pathway. Deletion of CRM1 in the cdc50Δ background normalized the abnormally high [Ca2+]c. Cdc50 interacts with Crm1 to maintain cellular calcium homeostasis. Analysis of chitin/chitosan content showed that deleting CRM1 reversed the decreased chitosan production of cdc50Δ cells. Together, these results demonstrate that Cdc50 and Crm1 regulation of the calcineurin pathway and cytoplasmic calcium homeostasis may underlie caspofungin resistance in C. neoformans. IMPORTANCE Cryptococcus neoformans is the leading cause of fungal meningitis, accounting for ∼15% of HIV/AIDS-related deaths, but treatment options for cryptococcosis are limited. Echinocandins are the newest fungicidal drug class introduced but are ineffective in treating cryptococcosis. Our previous study identified the lipid flippase subunit Cdc50 as a contributor to echinocandin resistance in C. neoformans. Here, we further elucidated the mechanism of Cdc50-mediated caspofungin drug resistance. We discovered that Cdc50 interacts with the mechanosensitive calcium channel protein Crm1 to regulate calcium homeostasis and caspofungin resistance via calcium/calcineurin signaling. These results provide novel insights into echinocandin resistance in this pathogen, which may lead to new treatment options, as well as inform echinocandin resistance mechanisms in other fungal organisms and, hence, advance our understanding of modes of antifungal drug susceptibility and resistance.